The Effect of Work Life Balance, Organizational Commitment on Turnover Intention Through Job Satisfaction for Employees at PT X - Luthfia Melati Fefinda Pulungan; Tiarapuspa Tiarapuspa (Penerbit Jurnal Indonesia, 2025)
This research presents an investigation of the effect of Work Life Balance, Organizational Commitment on Turnover Intention through Job Satisfaction at PT X. PT X is a multinational company engaged in international or inter-country based logistics. Therefore, Work Life Balance, Organizational Commitment will affect Turn Over Intention through Job Satisfaction. The investigation was conducted by distributing questionnaires that presented several options regarding personal and work biodata, then question items based on the variables in this study. Namely Work Life Balance (WLB), Organizational Commitment (OC), Job Satisfaction (JS), Turnover Intention (TI). The questionnaires were distributed to employees in various divisions randomly and based on ethics and professionalism in research. Employees are the company's greatest asset, as we know the importance of life balance and employee commitment to the company on the intention to quit or change places of work through employee satisfaction with the company. When employees are satisfied with their workplace, they will have high performance and increase employee commitment to the company. This study aims to analyse WLB, OC towards IT through JS of workers at PT X focusing on administrative, supervisory, professional/technical, and almost all divisions. This is because PT X is a multinational company that develops its business that prioritises customer satisfaction in various countries including Indonesia, so that almost all divisions must fully contribute to the company. This makes it difficult for employees to balance their personal and work lives, resulting in employee resignations. Employee resignation and turnover are major concerns for employers as they incur large associated costs (Hom et al., 2017). The loss of one employee can result in up to 60% loss of profit and productivity for the organisation (Rowley & Purcell, 2001). Therefore, organisations try to save their employees by paying attention to employee retention in their organisation. Previous literature, reveals that various factors are involved that influence employees to stay or leave the organisation (Subramaniam et al., 2019). However, it is believed that work-life balance has a positive influence on employee behaviour (Koon, 2022). Work-life balance (WLB) has become a central issue in the modern world of work. The high demand for productivity and the ever-evolving availability of technology have created significant pressure for workers to balance the demands of work with their personal lives. The healthcare sector, as one of the most demanding sectors, is often highlighted in WLB studies. Job satisfaction is treated as a mediator in this study based on theoretical foundations and literature. For example, a person's behaviour is determined by his or her behavioural intention to do so. This intention is itself determined by the person's attitude and subjective norm towards the behaviour (Sheppard et al., 1988). Job satisfaction is an important human attitude that has the ability to influence behaviour. Therefore, job satisfaction can be tested as a mediator between work-life balance, employee retention, and turnover. (Deery & Jago, 2015) confirmed that job satisfaction is a suitable mediator between work-life balance and employee behaviour (Deery & Jago, 2015).